THE IMPACT OF ELECTRONIC GOVERNMENT PROCUREMENT SYSTEMS ON TRANSPARENCY IN PUBLIC SECTORS. A CASE STUDY OF UGANDA CIVIL AVIATION AUTHORITY, ENTEBBE. - ORISHABA OBVIOUS BEINOBWENGYE (UGANDA CHRISTIAN UNIVERSITY, 2024)
The onset of electronic government systems has reshaped how public entities operate, with great emphasis being laid on the enhancement of transparency and accountability. This research proposal examines how e-Government impacts transparency within public entities, basing the case study on the Uganda Civil Aviation Authority. Considering the fact that UCAA is a significant regulator of civil aviation in Uganda, this will provide a very unique opportunity to assess how new digital tools and techniques affect transparency in one of the most important regulatory areas. The research has a multi-dimensional approach by integrating quantitative data analysis with qualitative case study methods to assess the effectiveness of the e-Government system at UCAA in enhancing transparency. Precisely, the study intends to investigate multiple initiatives on e-Government implemented by UCAA, including digital reporting systems, online portals offering public services, and the automation of compliance monitoring tools. The indicators for transparency would be access to regulatory information, openness related to decision-making processes, and how citizen engagement platforms function. This will involve the comparison of the operational data of UCAA before and after e-Government systems implementation, complemented by interviews with stakeholders, including UCAA staff, industry professionals, and the public. The combined approach sets ground for eliciting tangible outcomes of the digital transformation on one hand, and the perceived improvement in transparency on the other. The expected findings will prove, to what extent the e-Government initiatives at UCAA have facilitated more openness and increased public trust, highlighting successful strategies in leveraging the digital tools for enhanced transparency and possible challenges or gaps in the existing implementation. Ultimately, this study is expected to provide insight into how e-Government can act to enhance transparency among regulatory bodies. A focus on UCAA allows this research to draw detailed recommendations on how best practices in regard to digital governance could be reached by both the aviation sector and the wider public administration in Uganda.